Role of atherosclerosis, clot extent, and penumbra volume in headache during ischemic stroke. (13th September 2016) - van Os, Hendrikus J.A.; Mulder, Inge A.; van der Schaaf, Irene C.; Kappelle, L. Jaap; Velthuis, Birgitta K.; Broersen, Alexander; Vos, Jan A.; Terwindt, Gisela M.; Schonewille, Wouter; Ferrari, Michel D.; Algra, Ale; van Walderveen, Marianne A.A.; et al.
Abstract : Objective: To investigate the role of large vessel atherosclerosis, blood clot extent, and penumbra volume in relation to headache in ischemic stroke patients. Methods: In this cross-sectional study, we performed noncontrast CT, CT angiography (CTA), and CT perfusion (CTP) in 284 participants from the Dutch Acute Stroke Study and Leiden Stroke Cohort within 9 hours after ischemic stroke onset. We collected headache characteristics prospectively using a semi-structured questionnaire. Atherosclerosis was assessed by evaluating presence of plaques in extracranial and intracranial vessels and by quantifying intracranial carotid artery calcifications. Clot extent was estimated by the clot burden score on CTA and penumbra volume by CTP. We calculated risk ratios (RRs) with adjustments (aRR) for possible confounders using multivariable Poisson regression. Results: Headache during stroke was reported in 109/284 (38%) participants. Headache was less prevalent in patients with than in patients without atherosclerosis in the extracranial anterior circulation (35% vs 48%; RR 0.72; 95% confidence interval [CI] 0.54–0.97). Atherosclerosis in the intracranial arteries was also associated with less headache, but this association was not statistically significant. Penumbra volume (aRR 1.08; 95% CI 0.63–1.85) and clot extent (aRR 1.02; 95% CI 0.86–1.20) were not related with headache. Conclusions: Headache in the early phase of ischemic stroke tends to occur less often in patients with atherosclerosis than in patients without atherosclerosis in the large cerebral arteries. This finding lends support to the hypothesis that vessel wall elasticity is a necessary contributing factor in the occurrence of headache during acute ischemic stroke.